Li5SnP3 – a Member of the Series Li10+4xSn2−xP6 for x=0 Comprising the Fast Lithium‐Ion Conductors Li8SnP4 (x=0.5) and Li14SnP6 (x=1). Issue 10 (27th January 2022) - Strangmüller, Stefan; Müller, David; Raudaschl‐Sieber, Gabriele; Kirchhain, Holger; van Wüllen, Leo; Fässler, Thomas F.
Abstract: The targeted search for suitable solid‐state ionic conductors requires a certain understanding of the conduction mechanism and the correlation of the structures and the resulting properties of the material. Thus, the investigation of various ionic conductors with respect to their structural composition is crucial for the design of next‐generation materials as demanded. We report here on Li5 SnP3 which completes with x =0 the series Li10+4 x Sn2− x P6 of the fast lithium‐ion conductors α ‐ and β ‐Li8 SnP4 ( x =0.5) and Li14 SnP6 ( x =1). Synthesis, crystal structure determination by single‐crystal and powder X‐ray diffraction methods, as well as 6 Li, 31 P and 119 Sn MAS NMR and temperature‐dependent 7 Li NMR spectroscopy together with electrochemical impedance studies are reported. The correlation between the ionic conductivity and the occupation of octahedral and tetrahedral sites in a close‐packed array of P atoms in the series of compounds is discussed. We conclude from this series that in order to receive fast ion conductors a partial occupation of the octahedral vacancies seems to be crucial. Abstract : The compound Li5 SnP3 completes for x=0 the series Li10+4 x Sn2− x P6 ( x =0–1) of lithium‐ion conducting phosphidostannates. The thorough investigation of the crystal structure as well as the materials properties applying X‐ray diffraction as well as NMR and electrochemical impedance spectroscopy allows for a detailed comparison of the materials structure‐property relationships, and thus, improves the understanding of the conduction mechanism within solid ion conductors.